Event Study of IPO in Indonesia: Pump-and-Dump & Flipping Strategy Analysis - Eka Sudarmaji; Sri Ambarwati; Aulia Keiko Hubbansyah; Shinta Budi Astuti (DINASTI RESEARCH, 2020)
There were three important IPO anomalies: the positive average initial return (improperly called short-term 'underpricing'), the long-term underperformance, and hot/cold IPO. The EVENT STUDY model explained the 'underpricing' based on the assumption that the underwriter sets the initial price equal to the market-perceived true value and investors were rational. IPO prices are affected by demand and supply. The idea of the model was to explore pump-and-dump and flipping patterns exhibited upon IPO anomalies event in Indonesia. Pump-and-dump is the strategy to manipulate stock prices, while flipping was stocks bought at the IPO and sold at early days ta listing date. This strategy oftentimes exhibits anomalous behavior. Some implications of this model for the IPO market were positive 1st-day initial return (IR) and a negative relation cumulative average abnormal 5-days abnormal return (CAAR-5days) for flipping strategy. The other was a relationship between underperformance cumulative average 30-days abnormal returns (CAAR-30days) and cumulative average 5-days (CAAR-5days) abnormal returns in terms of pump-and-dump strategy. Using the relation between the Characteristics (Size of issue, Board and Floating rate) and Macroeconomics Condition (Central Bank Rate, Inflation rate, USD/IDR exchange, and GDP growth), and the IR, a CAAR-5days and a CAAR-30days, this EVENT STUDY explained the existence of the pump-and-dump and flipping pattern in the Indonesian stock exchanges. The Authors implemented a multivariate analysis of variance (MANOVA) to test hypotheses regarding the effect of a three-variables dependent (the initial return, a 5-days abnormal return, and a 30-days abnormal return) into several dependent variables. Using the IPO data taken from 2015-2019, the paper found that this EVENT STUDY explained the existence of pump-and-dump and flipping patterns at the early trading of IPO stocks in the Indonesia Exchange Market.